Reframing Sufism: Abuya Dimyati’s Embodied Spirituality as a Model of Religious Moderation in Contemporary Islam - Mukhtar Hanif Zamzamy; Aminullah Elhady; Ubaidillah; Lailatul Usriyah (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
This study examines Abuya Dimyati’s Sufism as a model of religious moderation and spiritual wisdom in the modern era. The research is motivated by the growing crisis of spirituality, the rise of religious extremism, and the transformation of religious authority in the digital age. Using a qualitative approach with a library research design, this study analyzes primary sources such as Abuya Dimyati’s teachings, sermons, and documented practices, as well as relevant contemporary scholarly literature. Data were analyzed using content analysis and hermeneutic interpretation to uncover the epistemological, ethical, and social dimensions of his Sufism. The findings reveal that Abuya Dimyati’s Sufism is rooted in akhlaqi Sufism, emphasizing the integration of sharia and haqiqa through ethical transformation and spiritual discipline. His teachings embody four core values of religious moderation: rahmah (compassion), tawazun (balance), zuhud (simplicity), and tasamuh (tolerance). These values function as internal mechanisms of ethical regulation, shaping both individual consciousness and social interaction. Furthermore, his Sufism reflects an “embodied spirituality” that integrates spiritual practice with social engagement, contributing to community harmony. This study proposes Sufism as a transformative moderation framework encompassing epistemological, psychological, and socio-practical dimensions. It argues that Abuya Dimyati’s Sufism provides a relevant and integrative response to contemporary challenges, including digital religiosity, polarization, and the crisis of religious authority. The study contributes to the development of Sufism as a contextual and globally relevant paradigm for fostering moderate, inclusive, and humanistic religious life.